The use of smartphones in ophthalmology: technological development and application - Barbosa Neto, José de Paula; Dutra, Bárbara de Araújo Lima; de Castro e Silva, Sarah Rubia Sales; Ribeiro, João Crispim Moraes Lima (Journal of Health & Biological Sciences, 2021)
Objective: Technological development has promoted several advances in society, including the creation of smartphones, which have been increasingly used in medicine, especially in ophthalmology. This study aimed to review the use of smartphones in ophthalmology. Methods: In January of 2020, the MEDLINE and LILACS databases were selected to provide articles containing the terms “Ophthalmology” and “Smartphone”, filtering the results between the years of 2015 and 2019. The evaluated outcomes were finally included into the following categories in the discussion: “Visual acuity”, “Amblyopia and strabismus”, “Anterior segment”, “Posterior segment”, “Glaucoma”, “Community patient education and assistance” and “Neurophthalmology”. Results: Smartphones can be useful in several different areas of ophthalmology and can provide the patients better understating and adhesion to their treatment. Conclusion: Applications can be used as tools to facilitate the work of several professionals and improve the understanding of patients about their clinical conditions.